A study on levels of body mass index and waist-hip ratio among adult women in a tertiary care health facility - Priyadharsini, Rajendran; Raja, TAR; Prakash, Manivel; Yadav, Dhananjay (Progress in Nutrition, 2017)
Background and Aim: This study aimed to assess the nutritional status of adult literate women belonging to the upper socio-economic groups by using the body mass index (BMI) and waist-to-hip ratio as indicators. An attempt to find out the different factors and pattern of some disease conditions influencing these scenarios has also been done. Methodology: A descriptive cross-sectional study was undertaken with 150 Undergraduate (UG)/Postgraduate (PG) residents studying various courses in medicine, along with 150 nurses and 150 women residing in various residential quarters of Dhanvantari campus in Puducherry. Prior to the study, a written consent was obtained from all participants with measurement of their height, weight, waist and hip circumference. Results:  The proportion of standard weight, overweight and obese were 33.3%, 42.1%, and 24.6 % respectively. Undernutrition was present in 2.5% of the study subjects. It was found that about one-third of the subjects had normal BMI, however, the rest were either overweight or obese. The factors influencing BMI groups were age, occupation, physical activity and the number of children. Diabetes and hypertension were associated with overweight and obesity. Waist-to-hip ratio showed that about 75% of study subjects had higher (>0.8) values. Conclusion:  Even though healthy lifestyle is a major concern today, overweight/obesity has to become an increasing burden among adult literate women. Hence, appropriate measures to monitor the trend of body weight towards overweight/obesity among women should be undertaken on a routine basis.